FUNCTIONS OF SOCIAL ECOLOGY IN THE FIELD OF PUBLIC EDUCATION (Education in the 21st Century, 2023)
The purpose of the research carried out within the framework of the article is to analyze the functions of social ecology in the field of general education and to justify that there are necessary prerequisites for the inclusion of knowledge about social ecology in public school.The analysis of the functions of social ecology will show that students can acquire knowledge about social ecology during classroom hours by including relevant topics in the plans of teachers by adding a new component to the “ecology” course. Regarding the social, ecological, and valeological challenges of the time, this type of education will become an important part of a solution and contribute to the students' healthy socialization.The functions of social ecology are as follows: economic and legal, developing-promoting, valeological behavior and aesthetic taste formation of students, providing feedback, and prediction and prevention functions. Each function has its own importance for the development of the sector.The analysis emphasizes the importance of our social ecological knowledge. With digitalization and changing communication mechanisms in society, the system of relationships also changes.Conclusion. The analysis shows that the students' knowledge of social ecology is relevant in our country. It promotes and develops students' approaches to the complete system of nature-society, valeological behavioral changes, and valuing nature in maintaining society.Learners can acquire knowledge about social ecology during classroom hours, as a result of the appropriate plan, instructions, and ecology textbook.
Keywords: Social ecology; functions of social ecology; patterns of social ecology; contradictions in the development of ecological problems; social ecological knowledge